2015
DOI: 10.1089/jwh.2014.5001
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Posttraumatic Stress Disorder Among Women with Vulvodynia: Evidence from the Population-Based Woman to Woman Health Study

Abstract: Background: Psychological disorders may affect the pain experience of women with vulvodynia, but evidence remains limited. The present study aimed to describe the magnitude of the association of depression and posttraumautic stress disorder (PTSD) with the presence of vulvodynia in a nonclinical population from southeastern Michigan. Methods: Baseline data from 1,795 women participating in the Woman to Woman Health Study, a multiethnic population-based study, was used for this analysis. Validated screening que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…DPSD in men is analogous to vulvodynia in women, and there have been calls to use a similar classification system . Women with vulvodynia experience chronic burning vulval pain and frequently have psychosocial comorbidities . It has already been suggested that vulvodynia may also reflect a somatization disorder, yet dermatologists still seem to persist with largely useless treatments directed against neuropathic pain for this condition too.…”
Section: Discussionmentioning
confidence: 99%
“…DPSD in men is analogous to vulvodynia in women, and there have been calls to use a similar classification system . Women with vulvodynia experience chronic burning vulval pain and frequently have psychosocial comorbidities . It has already been suggested that vulvodynia may also reflect a somatization disorder, yet dermatologists still seem to persist with largely useless treatments directed against neuropathic pain for this condition too.…”
Section: Discussionmentioning
confidence: 99%
“…• Many women with LPV report premorbid anxiety, mood disorders (72), PTSD (73) and sexual/physical abuse in childhood (74) why psychological factors may be important.…”
Section: Vulvodyniamentioning
confidence: 99%
“…In baseline data on 250 Veterans Affairs primary care patients, depression and PTSD were independently and significantly related to higher pain reports, as well as to higher rates of disability and lower quality of life [1]. As to relevant studies targeting women in particular, 2015 research showed that depressed women and women who screened positive for PTSD had a higher prevalence of having the pain disorder vulvodynia, which is indicative of the fact that 1) those two disorders can contribute to the probability of experiencing vulvodynia, or 2) as the study's authors pointed out, depression, PTSD, and vulvodynia share patho-physiological as well as risk profiles [106]. Table 1 offers a concise summary of the review provided herein.…”
Section: A Potential Explanation Of Comorbidity Of Depression Ptsd mentioning
confidence: 99%